Canine Mast Cell Tumour Lomustine’s Sensitization by Tyrosine Kinase Inhibitors - de Souza, Larissa Marchetti de Souza; Lima Gorza, Leonardo; Rassele Merísio, Alice Correa; de Sena, Bruna Voltolin; Almeida, Isabella Oliveira; Cunha Flecher, Mayra; dos Santos Horta, Rodrigo (Acta Scientiae Veterinariae, 2022)
Background: Tyrosine kinase inhibitors (TKIs) may sensitize neoplasms to conventional antineoplastic agents, however such studies are scarse in the veterinary literature and there is no in vivo study about this subject. Although the literature recommend consensual about the use of masitinib for unresectable or metastatic MCTs, the potential of tumour sensitization to chemotherapeutic agents exerted by the drug is poorly explored in veterinary medicine. The objective of this paper was to report, for the first time, the sensitization of 2 canine mast cell tumours (MCTs) to lomustine, with the use of 2 tyrosine kinase inhibitors: masitinib and toceranib. Cases: Two dogs were referred due tumour recurrence in the left pelvic limb (dog 1), and unilateral mass in the right nasal mucocutaneous region (dog 2). The first case was a 8-year-old female Pinscher, and the second case refers to a 8-year-old male mixed-breed dog. Fine needle aspiration of both lesions was performed, and the cytological analysis were compatible with high grade canine MCT. In the first case, it was started a chemotherapeutic treatment with intravenous vinblastine (2 mg/m²), associated with prednisolone (40 mg/m2, every 24 h for 7 days), followed by 25 mg/m2 every 24 h, for more 30 days, tramadol (4 mg/kg every 8 h, until new recommendations) and gabapentin (3 mg/kg every 12 h, until new recommendations). However, there was no objective response, and vinblastine was substituted by lomustine (60 mg/m2 every 21 days), however there was also no response after 2 doses. After masitinib importation, the same was started at 12.5 mg/kg orally every 24 h, but there was also no objective response. However, after new lomustine administration the lesion showed complete remission. The second dog initiated its treatment with toceranib, recently licensed in Brazil, at a dosage of 2.7 mg/kg every 48 h, and after 30 days, there was partial remission. However, the remaining lesion still deemed unresectable, and systemic chemotherapy with lomustine (50 mg/m2) was initiated along with continuous toceranib. After 3 weeks of the first chemotherapy complete remission was noted and a second dose was administered. Once the patient remained in complete clinical remission, only toceranib was maintained at the same dose. After 11 months using the toceranib, there was sign of disease recurrence and lomustine was re-initiated resulting in complete remission. Discussion: The TKIs masitinib and toceranib might be considered the first-line therapy for unresectable and/or metastatic canine MCT, but also for those cases with confirmed internal tandem duplications in the exon 11 of the c-KIT protooncogene. Masitinib appears to be more selective than others TKI, such as toceranib, imatinib, dasatinib and sunitinib, because it causes weak inhibition of BCR/ABL (breakpoint cluster region-Abelson), Fms (macrophage colony-stimulating factor receptor), Flt-3 (FMS-like tyrosine kinase-3) and VEGFR (vascular endothelial growth factor receptor), which may partially explains its increased safety and lower risk of cardiotoxicity. In the first case, the animal has been treated with lomustine associated to masitinib and showed a progression-free interval of 33 days, however, the response reported may have been lower, due previously exposition to chemotherapeutic agents, which might compromise the response to TKI. The second case, with the association of lomustine and toceranib, was followed up for 365 days, presenting only one recurrence in the final third of the follow-up, however, with subsequent new complete remission. Sensitization of canine MCT to lomustine with TKIs increases the therapeutic possibilities for this neoplasm, mainly in patients with advanced stage and high-grade tumours. Keywords: dog, mast cell, chemotherapy, masitinib, toceranib.